Foreign Trade of the Democratic Republic of the Congo and the Share of Agricultural Products for Export - Kalala, Jean Rene; Hanchar, Andrei; Witkowska-Dąbrowska, Mirosława (Olsztyn Economic Journal, 2020)
Despite its numerous resources, the Democratic Republic of the Congo is one of the poorest countries in the world. The DRC also has underutilised resources of arable land and good conditions for agricultural production. This study analysed changes in the volume of foreign trade in the DRC and assessed the share of its agricultural exports in the years 2015-2019. The analysis covered the volume of total imports and exports, as well as imports and exports by sector. The foreign trade balance and the dynamics of change in the years under analysis were calculated. Structural indicators as well as fixed and variable-based dynamic indices were used. As a result of the conducted research, fluctuations in the export of all goods were found along with a decrease in the export of numerous significant agriculturally produced goods: rubber, palm oil and medicinal plants.